UN EFFORTS IN RESOLVING THE ABYEI CONFLICT BETWEEN SUDAN AND SOUTH SUDAN - Averil, Abyan Dhamar (Journal of Social Political Sciences, 2024)
<div class="min-h-8 text-message flex w-full flex-col items-end gap-2 whitespace-normal break-words text-start [.text-message+&]:mt-5" dir="auto" data-message-author-role="assistant" data-message-id="a1a83477-68ab-4baa-869d-541e4ae51709" data-message-model-slug="gpt-4o"> The conflict in the Abyei region between Sudan and South Sudan is a protracted issue driven by historical, ethnic, and resource-based factors. This study investigates the role of the United Nations in addressing the Abyei conflict, with a focus on the peacekeeping missions of UNISFA, UNMIS, and UNMISS. Employing a qualitative research methodology, the study analyzes data related to the peace efforts and their impact on the region. The research utilizes the conflict resolution framework to explore how the United Nations has contributed to managing and mitigating the conflict between Sudan and South Sudan, particularly in Abyei. The findings highlight the importance of the UN’s involvement in facilitating dialogue, supporting peace negotiations, and conducting peacekeeping operations. The study concludes that while significant progress has been made, the success of peacebuilding efforts in Abyei hinges on continued cooperation between the Sudanese and South Sudanese governments, with sustained support from international organizations. Achieving lasting peace in Abyei requires collaborative efforts and a comprehensive approach to conflict resolution.